Towards net zero by data-driven discovery of sustainable cement alternatives - Jack D. Evans (Communications Chemistry)
The construction industry faces mounting pressure to reduce its carbon footprint, with cement production alone contributing over 6% of global greenhouse gas emissions. In recent work, machine learning models screened over 14,000 materials from scientific literature and 1 million rock samples, identifying a diverse set of secondary and natural materials that could partially replace global cement production.